2021
DOI: 10.1093/mnrasl/slab109
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics beats dust: unveiling nested substructure in the perturbed outer disc of the Milky Way

Abstract: We use the Gaia eDR3 data and legacy spectroscopic surveys to map the Milky Way disc substructure towards the Galactic Anticenter at heliocentric distances $d\ge 10\, \rm {kpc}$. We report the discovery of multiple previously undetected new filaments embedded in the outer disc in highly extincted regions. Stars in these over-densities have distance gradients expected for disc material and move on disc-like orbits with $v_{\phi }\sim 170-230\, \rm {km\, s^{-1}}$, showing small spreads in energy. Such a morpholo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
4
13
1
2
Order By: Relevance
“…In the case of the Milky Way (MW) disk, which can be studied in much greater detail than any other system, recent data from astrometric and radial velocity surveys such as SEGUE (Yanny et al 2009), RAVE (Steinmetz et al 2006), GALAH (Bland-Hawthorn et al 2019), LAMOST (Cui et al 2012), and above all Gaia (Gaia Collaboration et al 2016, 2018a, 2018b have revealed a variety of additional vertical distortions. At large galactocentric radii (>10 kpc) this includes, among others, oscillations and corrugations (Xu et al 2015;Schönrich & Dehnen 2018), and streams of stars kicked up from the disk that undergo phase mixing, sometimes referred to as "feathers" (e.g., Price-Whelan et al 2015;Thomas et al 2019;Laporte et al 2022). Similar oscillations and vertical asymmetries have also been reported in the solar vicinity (e.g., Widrow et al 2012;Williams et al 2013;Yanny & Gardner 2013;Gaia Collaboration et al 2018b;Quillen et al 2018;Bennett & Bovy 2019;Carrillo et al 2019).…”
Section: Introductionmentioning
confidence: 59%
“…In the case of the Milky Way (MW) disk, which can be studied in much greater detail than any other system, recent data from astrometric and radial velocity surveys such as SEGUE (Yanny et al 2009), RAVE (Steinmetz et al 2006), GALAH (Bland-Hawthorn et al 2019), LAMOST (Cui et al 2012), and above all Gaia (Gaia Collaboration et al 2016, 2018a, 2018b have revealed a variety of additional vertical distortions. At large galactocentric radii (>10 kpc) this includes, among others, oscillations and corrugations (Xu et al 2015;Schönrich & Dehnen 2018), and streams of stars kicked up from the disk that undergo phase mixing, sometimes referred to as "feathers" (e.g., Price-Whelan et al 2015;Thomas et al 2019;Laporte et al 2022). Similar oscillations and vertical asymmetries have also been reported in the solar vicinity (e.g., Widrow et al 2012;Williams et al 2013;Yanny & Gardner 2013;Gaia Collaboration et al 2018b;Quillen et al 2018;Bennett & Bovy 2019;Carrillo et al 2019).…”
Section: Introductionmentioning
confidence: 59%
“…porte et al. 2018, 2022), which could persist for significant amounts of time (Laporte et al 2022). Laporte et al (2018) favor the Sagittarius dwarf galaxy (Ibata et al 1994;Law & Majewski 2010) as the main perturber, but the Large Magellanic Cloud could also play a role (see also Weinberg & Blitz 2006).…”
Section: Complex C and The Outer Galaxy High-velocity Cloudsmentioning
confidence: 99%
“…A combination of dynamical and chemical data on thick disk stars is required to distinguish between these various scenarios. In particular, the long dynamical times, especially in the outer disk, result in a persistent memory of past perturbations, either secular or external, which have created lasting Galactic warps and flares (Momany et al 2006;Minchev et al 2015;Laporte et al 2021).…”
Section: The Formation History Of the Milky Way Thick Diskmentioning
confidence: 99%

Overview of the DESI Milky Way Survey

Cooper,
Koposov,
Prieto
et al. 2022
Preprint
Self Cite